Kunstfotografie rond 1900 - Harker, Margaret; Andries, Pool; Coenen, Roger (s.l. : Gemeentekrediet, 1983)
Alexandre ; Annan, James Craig ; Berssenbrugge, Henri ; Brigman, Anne W. ; Coburn, Alvin Langdon ; Cochrane, Archibald ; Curtis, Edward Sheriff ; Davison, George ; Day, Fred. Holland ; Demachy, Robert ; Dubreuil, Pierre ; Eickemeyer Jr, Rudolf et al.
Kunstfotografie rond 1900, Passage 44, Brussel, 6 mei - 3 juli 1983
boek